2005
DOI: 10.1557/jmr.2005.0124
|View full text |Cite
|
Sign up to set email alerts
|

Inverse scaling functions in nanoindentation with sharp indenters: Determination of material properties

Abstract: This paper, based on extensive finite element simulations and scaling analysis, presents scaling functions for the inverse problem in nanoindentation with sharp indenters to determine material properties from nanoindentation response. All the inverse scaling functions were directly compared with results calculated using the large deformation finite element method and are valid from the elastic to the full plastic regimes. To relate the material properties to measurable indentation parameters a new nondimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 30 publications
0
39
0
1
Order By: Relevance
“…1,2 Subsequently, several methods using multiple sharp-tipped indenters have been developed to extract plastic properties, [3][4][5][6][7][8] although these methods still present a degree of inconvenience when operating with these indenters. In changing to spherical indentation, various authors have demonstrated that, by analyzing the force-depth curves, it is possible to determine material plastic properties.…”
Section: And ð1þmentioning
confidence: 99%
“…1,2 Subsequently, several methods using multiple sharp-tipped indenters have been developed to extract plastic properties, [3][4][5][6][7][8] although these methods still present a degree of inconvenience when operating with these indenters. In changing to spherical indentation, various authors have demonstrated that, by analyzing the force-depth curves, it is possible to determine material plastic properties.…”
Section: And ð1þmentioning
confidence: 99%
“…Such isotropic continuum simulations have provided an insight into the contact mechanics of strain hardening solids and constitute a robust, yet flexible tool to the development of methodologies for mechanical property extractions from indentation experiments (for sharp indentation, see, e.g., Bucaille et al, 2003;Chollacoop et al, 2003;Alcalá , 2003, Cao andLu, 2004;Casals and Alcalá , 2005;Wang et al, 2005;Tho et Alkorta et al, 2005;Ogasawara et al, 2006;Kim et al, 2006;Chollacoop and Ramamurty, 2006;. In the other spectrum of material length scales, atomistic and discrete dislocation dynamics simulations are shedding light into the mechanics of dislocation emission, the individual interactions between dislocations, and on the interplay between grain boundaries and dislocations in ultra low-load nano-indentation experiments (e.g., Kelchner et al, 1998;Fivel et al, 1998;Lilleodden et al, 2003;Feichtinger et al, 2003;Ma and Yang, 2003;Zhu et al, 2004, Shen andLeger, 2004;Yoon et al, 2004;Lee et al, 2005;Shiari et al, 2005;Saraev and Miller, 2006;Minor et al, 2006;Tsuru and Shibutani, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As it is generally difficult to derive accurate analytical expressions for the indentation response of materials, numerical finite element simulations have been developed to address two classes of problems: (i) the 'forward problem' -where the characteristics of the indentation response are predicted from known material elasto-plastic properties, and (ii) the 'reverse problem' -where the material elasto-plastic properties are estimated from the measured indentation responses (e.g. [40][41][42][43][44][45]). By combining numerical simulations with dimensional analysis, the corresponding 'forward' and 'reverse' algorithms have been developed to characterize the indentation response of select classes of materials, such as the powerlaw hardening metallic materials.…”
mentioning
confidence: 99%